Step
*
1
2
1
1
1
1
of Lemma
p-unit-part-unique
1. p : {2...}
2. j : ℕ
3. k : ℕ
4. b : p-units(p)
5. a : p-units(p)
6. p^j(p) * b = p^j * p^(k - j)(p) * a ∈ p-adics(p)
7. j < k
8. p^(k - j)(p) * a = b ∈ p-adics(p)
⊢ j = k ∈ ℤ
BY
{ (Assert (p^(k - j)(p) * a 1) = (b 1) ∈ ℤ BY
         Auto) }
1
1. p : {2...}
2. j : ℕ
3. k : ℕ
4. b : p-units(p)
5. a : p-units(p)
6. p^j(p) * b = p^j * p^(k - j)(p) * a ∈ p-adics(p)
7. j < k
8. p^(k - j)(p) * a = b ∈ p-adics(p)
9. (p^(k - j)(p) * a 1) = (b 1) ∈ ℤ
⊢ j = k ∈ ℤ
Latex:
Latex:
1.  p  :  \{2...\}
2.  j  :  \mBbbN{}
3.  k  :  \mBbbN{}
4.  b  :  p-units(p)
5.  a  :  p-units(p)
6.  p\^{}j(p)  *  b  =  p\^{}j  *  p\^{}(k  -  j)(p)  *  a
7.  j  <  k
8.  p\^{}(k  -  j)(p)  *  a  =  b
\mvdash{}  j  =  k
By
Latex:
(Assert  (p\^{}(k  -  j)(p)  *  a  1)  =  (b  1)  BY
              Auto)
Home
Index